The activities and impact of personalisation in a UK business school. Issue 9 (21st October 2019) - Jones, Adam; Yazdani, Baback; Barton, Harry
ABSTRACT: The aim of this study was to consider the activities and impact of personalisation in a UK higher education setting. It considered how personalisation has affected outputs in terms of progression, achievement, internship, enterprise project and international placement uptake within the Nottingham Business School at Nottingham Trent University. Qualitative and quantitative data were collected. Semi-structured interviews were carried out with members of the personalisation team and those delivering personalisation. The quantitative data pertains to outputs in terms of success rates, particularly with regard to when the personalisation project began, in 2015/16. The findings suggest that the personalisation process involved engagement, interaction and reflection to meet the needs and requirements of the learner; it also provided them with options. This contributes to improving success rates, particularly when the Personalisation project began.